THE INVESTIGATION OF ANXIETY ON ENGLISH LANGUAGE LEARNING IN HIGH SCHOOL STUDENTS: A CASE STUDY IN GRADE ELEVENT - Lestari, Dina Aprillia; Ma’mun, Akhmad Haqiqi; Ahmad, Zuhad (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2024)
This research aims to investigate the impact of anxiety on English language learning achievements among high school students. It identifies anxiety as a significant emotional condition that can either hinder or motivate language acquisition. The study focuses on 11th-grade students at SMAN 106 Jakarta and examines various factors contributing to anxiety, including internal elements such as perception, personality, and intelligence, as well as external factors like motivation, classroom environment, and cognitive characteristics. The research highlights that anxiety can lead to feelings of restlessness, frustration, self-doubt, and tension. This emotional state often results in fear of negative evaluation, nervousness about making mistakes, and concerns about others' language abilities. Utilizing a descriptive qualitative research approach, the study employs questionnaires and in-depth interviews to collect data from students. Findings suggest that anxiety is a multifaceted issue, with students experiencing anxiety due to a range of factors including fear of criticism, judgment, and low grades. The research aims to provide valuable insights into the challenges faced by high school students and emphasize the need for tailored interventions and support mechanisms to help manage and alleviate anxiety. This understanding is intended to assist both teachers and students in addressing and overcoming the barriers posed by anxiety in language learning.